Understanding Digital Transformation Village Credit Institutions Towards Sustainability Based on Local Genius - Darmayasa, I Nyoman (Jurnal Ilmiah Akuntansi & Bisnis, 2024)
This study aims to understand the digitization transformation of village credit institutions towards sustainability based on local genius. Local geniuses are fundamental values for village credit institutions to enrich traditional local citizens. This research was conducted in village credit institutions and has since been transformed into digital. This research employed the combination methodology of Participatory Action Research in developing the application and Nusantara Paradigm as a view and the method using local values in implementing the application. Data were collected through in-depth interviews with stakeholders’ village credit institutions in Bali Province, the heads of village credit institutions, which is a digital transformation. This study realizes that window-dressing is a common practice that can be described using agency theory. Window dressings can be reduced through digital transformations. Sustainability exists as an enrichment of traditional local economics based on local genius with three harmonized relationships with God, humans, and the environment. Local genius not just the values written in regulation or standard operating procedures, but internalization in daily operational village credit institutions. Sustainability existence and growth measure with the comprehensive approach, harmonization with the God in our spiritual values, harmonization with the human through transparent report can be describe with development Humanism Agency Theory on Traditional Social Community Ownership. Harmonization in an environment with practical digital transformation to save our planet. The originality of this research is that it extends agency theory type 4 in accordance with social community ownership of a new type of conflict. The combined method of Participatory Action Research in developing the application and Nusantara Paradigm in implementing a new methodology approach reflecting digital process transformation based on local values.